Anticoagulation Management for Impella Percutaneous Ventricular Assist Devices: An Analysis of a Single-Center Experience. Issue 11 (November 2020) - Wood, Ethan; Hayes, Charles; Hart, Anthony
Background: Impella devices offer temporary mechanical circulatory support for cardiogenic shock. The manufacturer recommends systemic anticoagulation with a target activated clotting time of 160 to 180 s but provides no guidance on how to manage both the heparinized purge solution and the additional intravenous heparin needed to reach this therapeutic range. Previous publications demonstrated a lack of standardization in heparin management for Impella devices. Objective: The purpose of this study was to compare the effectiveness and safety of 2 different heparin protocols for long-term Impella support. Methods: This single-center, retrospective study included adult patients on Impella support for greater than 24 hours. The primary end point was time to therapeutic range measured in hours, from time of implantation to the first of 2 consecutive measurements within the therapeutic range. Secondary end points included percentage of time in therapeutic range, rates of major bleeding, pump thrombosis, hemolysis, and nursing satisfaction. Results: There were 19 patients identified, with 7 using the original protocol and 12 using the revised protocol. Time to therapeutic range was similar between protocols (15.5 vs 12 hours, P = NS). Another 14 patients were managed with patient-specific protocols as a result of bleeding or physician preference. In total, 42% of all patients in this study experienced major bleeding. There were no confirmed thrombosis events. This study was limited by a small sample size. Conclusion and Relevance: Despite using different heparin protocols, outcomes and bleeding events were similar between groups. Future studies are needed to determine the optimal degree of anticoagulation necessary to reduce bleeding risk.